Geographic variation in the eukaryotic virome of human diarrhea - Holtz, L.; Cao, S.; Zhao, G.; Bauer, I.; Denno, D.; Klein, E.; Antonio, M.; Stine, O.; Snelling, Thomas; Kirkwood, C.; Wang, D. (Reed Elsevier, 2014)
© 2014 Elsevier Inc. Little is known about the population of eukaryotic viruses in the human gut ("virome") or the potential role it may play in disease. We used a metagenomic approach to define and compare the eukaryotic viromes in pediatric diarrhea cohorts from two locations (Melbourne and Northern Territory, Australia). We detected viruses known to cause diarrhea, non-pathogenic enteric viruses, viruses not associated with an enteric reservoir, viruses of plants, and novel viruses. Viromes from Northern Territory children contained more viral families per sample than viromes from Melbourne, which could be attributed largely to an increased number of sequences from the families Adenoviridae and Picornaviridae (genus enterovirus). qRT-PCR/PCR confirmed the increased prevalence of adenoviruses and enteroviruses. Testing of additional diarrhea cohorts by qRT-PCR/PCR demonstrated statistically different prevalences in different geographic sites. These findings raise the question of whether the virome plays a role in enteric diseases and conditions that vary with geography.